Adaptation strategies to cope with the effects of Climate variability in the Central Plateau region of Burkina Faso - Zoma Vincent (Zbornik radova Departmana za geografiju, turizam i hotelijerstvo)
Climate variability presents major challenges across Africa, particularly in Burkina Faso. This article analyses the adaptation strategies implemented by local populations and development actors to cope with this phenomenon in the Central Plateau region. Conducted in October 2023 in three villages in the region, the research combines field observations, semi-structured interviews and documentary research. The results reveal a range of coping strategies adopted by local people. In agriculture, these include the use of short-cycle varieties, the planting of trees to counter the high heat, and soil conservation techniques to combat drought. Livestock farmers have also developed strategies such as transhumance and the construction of shelters adapted to the climate. In market gardening, the use of compost and innovative irrigation techniques is widespread. Development players, particularly technical services and NGOs, are supporting these initiatives by promoting sustainable agricultural practices and encouraging the construction of resilient infrastructure. This article thus highlights the importance of local adaptation to climate change and the crucial role of development players in strengthening community resilience to climate variability.